Mixed Methods Investigation of a Pro-environmental Behaviour: The Case of Reusable Coffee Cups - Novoradovskaya, Elizaveta (Curtin University, 2021)
In her thesis Lisa explored a pro-environmental behaviour of using a reusable cup, establishing its determinants and then applying them to a behaviour change intervention to increase that behaviour.